Therapeutic hypothermia in patients following traumatic brain injury: a systematic review. Issue 3 (6th May 2016) - Dunkley, Steven; McLeod, Anne
ABSTRACT: Background: The efficacy of therapeutic hypothermia in adult patients with traumatic brain injury is not fully understood. The historical use of therapeutic hypothermia at extreme temperatures was associated with severe complications and led to it being discredited. Positive results from animal studies using milder temperatures led to renewed interest. However, recent studies have not convincingly demonstrated the beneficial effects of therapeutic hypothermia in practice. Aim: This review aims to answer the question: in adults with a severe traumatic brain injury (TBI), does the use of therapeutic hypothermia compared with normothermia affect neurological outcome? Design: Systematic review. Method: Four major electronic databases were searched, and a hand search was undertaken using selected key search terms. Inclusion and exclusion criteria were applied. The studies were appraised using a systematic approach, and four themes addressing the research question were identified and critically evaluated. Results: A total of eight peer‐reviewed studies were found, and the results show there is some evidence that therapeutic hypothermia may be effective in improving neurological outcome in adult patients with traumatic brain injury. However, the majority of the trials report conflicting results. Therapeutic hypothermia is reported to be effective at lowering intracranial pressure; however, its efficacy in improving neurological outcome is not fully demonstrated. This review suggests that therapeutic hypothermia had increased benefits in patients with haematoma‐type injuries as opposed to those with diffuse injury and contusions. It also suggests that cooling should recommence if rebound intracranial hypertension is observed. Conclusion: Although the data indicates a trend towards better neurological outcome and reduced mortality rates, higher quality multi‐centred randomized controlled trials are required before therapeutic hypothermia is implemented as a standard adjuvant therapy for treating traumatic brain injury. Relevance to clinical practice: Therapeutic hypothermia can have a positive impact on patient outcome, but more research is required.